Palaeomagnetism of the Southern Zone of the Lewisian (Precambrian) Foreland, NW Scotland - Smith, R. L.; Piper, J. D. A. (Geophysical Journal International, 1982)
Palaeomagnetic results are reported from 111 localities in meta- morphic rocks from the Southern Zone of the Lewisian Complex and 12 sites from similar terrain on the island of Lewis and Harris. These rocks were magnetized during slow uplift following the ca. 1800 Ma Laxfordian tectonic/magmatic episode. The Southern Zone experienced diachronous uplift and there is a transition from predominantly positive NW remanence directions in the north to shallow negative NW directions in the south. More prolonged metamorphism in the south correlates with a transition from magnetite/sulphide to magnetite/hematite assemblages. The relict Ruadh Mheallan zone relatively unaffected by Laxfordian tectonism preserves a (A1) remanence D =82°, I =65° which is sporadically recovered as high blocking temperature component in areas bordering this zone. Elsewhere, the migration of field directions is summarized as mean directions (A3) D =323°, I =44°, (A4) D =314°, I =14° and (A5) D =313°, I =- 11° which appear to follow on sequentially from the predominant A2 direction ( D =286°, I =55°) observed in the Central Zone of the Lewisian Complex. The remanence directions are linked to a first approximation to the K-Ar hornblende ages and imply a migration of the ambient field direction through ca. 110° during an interval between 1 × 107 and 2 × 108× yr at about 1600 Ma; the weight of the evidence suggests that the interval represented is between 0.5 and 1 × 108× yr. The Lewisian A2–A5 directions yield palaeopoles which follow on from 1800–1700 Ma magnetizations from the Hudsonian terrains of Greenland and North America and overlap with the youngest record from these regions on the pre-drift reconstruction; collectively the data define part of a large apw loop.